Seismic base isolation for buildings in regions of low to moderate seismicity: practical alternative design - Islam, A.B.M.S.; Ahmad, Syed Ishtiaq; Jameel, M.; Jumaat, Mohd Zamin (Practice Periodical on Structural Design and Construction, 2010)
lthough Dhaka city has experienced any moderate to large earthquakes in the past, some recent ground shakings are certainly indications of its earthquake source and vulnerability. In addition, microseismicity data also supports the existence of at least four earthquake source points in and around Dhaka. However, it is important to appropriately consider the seismic lateral load effect in structural design. A newly adopted technology of seismic design is to isolate the superstructure from the substructure with the use of a base isolator. This paper covers the design of base isolators for a building located in Dhaka, Bangladesh, along with its structural and economic feasibility. A time history is generated for Dhaka, adjusting peak ground acceleration as per seismic region from a nearby recorded earthquake. The response spectrum curve based on the site geology of Dhaka is also generated from this time history. Linear static as well as dynamic (time history and response spectrum) analyses have been carried out for both isolated and nonisolated buildings. Similar analyses have also been repeated for buildings with different heights but similar plan areas. The study reveals that for low-to medium-rise buildings, isolation can reduce seismic force along with some savings in structural cost of the building, though incorporating base isolators increase the overall price and installation cost. A meticulous review indicates that savings may be in the order of 5â10 of the total structural cost of the respective building.